Recurrent aggressive angiomyxoma - Alencar,Suelene Suassuna Silvestre de (2013)
INTRODUCTION: aggressive angiomyxoma is a highly aggressive, rare neoplasm of the mesenchymal tissue with a high recurrence rate. It represents an important differential diagnosis of pelvic tumors in women of reproductive age. This study aims to describe a case of aggressive angiomyxoma. CASE REPORT: woman, 37 years old, complained about a bulge on the right perianal region, and anal itching and burning, bleeding, tenesmus and incontinence. The proctologic examination confirmed the perianal bulge and extrinsic compression of the posterior wall of the rectum. Computed tomography (CT) of the pelvis showed a well-defined pelvic mass extending to the right rectal area. Exploratory laparotomy showed a mass of fibro elastic consistency adjacent to the pelvic organs and closely attached to the distal rectum, and performed a resection of the pelvic tumor afterward. Anatomopathological analysis revealed an aggressive angiomyxoma. Magnetic resonance imaging (MRI) of the pelvis showed signs of recurrence in the pelvic cavity on the right side of the rectum. A surgical procedure was performed to resect the lesion. After an asymptomatic period, the MRI showed solid growths located in the right ischiorectal fossa. A new surgical procedure identified only retention cysts in the pelvis and right ischiorectal fossa, only lysis of adhesions was performed. The patient is currently undergoing follow-up without disease recurrence.